PENGARUH GAYA HIDUP DAN CITRA MEREK TERHADAP PENGAMBILAN KEPUTUSAN PELANGGAN - Rahmat, Abdul (Jurnal Manajemen, 2017)
The development of cosmetics industry in Indonesia is currently in good condition. People, especially women, are increasingly aware of the importance of cosmetics ranging from the use for important events to as daily necessities. The roles of lifestyle through activity, interest, and opinion play a major role in determining a person's decision especially in terms of making a purchase (Sathis and Rajamohan, 2008). Other than lifestyle brand image play and important role in customer buying decision of lipstick. Path analysis are conducted in order to determine the impact of both factor on buying decision.Furthermore, the method analyze the causal relationships that occur in multiple regression analysts if the independent variables affect other variables either partially or simultaneously.Results show the significance of the model which show that both lifestyle and brand image gave impact on lipstick buying decisionby 75.6% and 24.4% are influenced by other variables not explained in the research. All in all it become more concise to say that lifestyle and brand image are take depth root in customer decision making processes.